SIKAP MAHASISWA FAKULTAS TARBIYAH IAIN SORONG TERHADAP PROFESI KEGURUAN - Afroh Nailil Hikmah; Indah Ayu Permatasari; Ita Diah Purnama Sari (MISOOL: Jurnal Pendidikan Dasar, 2020)
Students of the Faculty of Tarbiyah as prospective teachers are expected to have a positive attitude towards the Teaching Profession so that they will display a good perception and satisfaction with the forerunner, future work, and high work motivation, which in turn will reflect a prospective teacher who is able to work professionally and has competence high professional. This study aims to reveal the attitudes of students of the Faculty of Tarbiyah as prospective teachers towards the Teaching Profession, and whether prospective teachers have a positive attitude towards the Teaching Profession. In this research, what is meant by the attitude of prospective teacher students towards the Teaching Profession is a tendency of a prospective teacher in responding to the likes or dislikes of the Teaching Profession, which is ultimately expressed in the form of actions or behaviors related to the prospective Profession, this research is a descriptive study. Which uses a survey method using a questionnaire. The population in this study were student teacher candidates at the Tarbiyah Faculty of IAIN Sorong, in this study the research sample was taken using a questionnaire, namely the sampling technique by looking at the distribution that represents the questions with a total sample of 61 people. The data collection technique used a half-open questionnaire method. The results of the study were analyzed by paying attention to the proportion of each student teacher's attitude towards the questionnaire given by the percentage technique. The results showed that most of the students of the Tarbiyah Faculty of IAIN Sorong as prospective teachers had a positive attitude towards the Teaching Profession